Insights into the mechanism regulating the differential expression of the P28-OMP outer membrane proteins in obligatory intracellular pathogen Ehrlichia chaffeensis - Duan, Nan (Emerg Microbes Infect, 2021)
Ehrlichia chaffeensis causes human monocytic ehrlichiosis (HME), which is one of the most prevalent, life-threatening emerging infectious zoonoses. The life cycle of E. chaffeensis includes ticks and mammals, in which E. chaffeensis proteins are expressed differentially contributing to bacterial survival and infection. Among the E. chaffeensis P28-OMP outer membrane proteins, OMP-1B and P28 are predominantly expressed in tick cells and mammalian macrophages, respectively. The mechanisms regulating this differential expression have not been comprehensively studied. Here, we demonstrate that the transcriptional regulators EcxR and Tr1 regulate the differential expression of omp-1B and p28 in E. chaffeensis. Recombinant E. chaffeensis Tr1 bound to the promoters of omp-1B and p28, and transactivated omp-1B and p28 promoter-EGFP fusion constructs in Escherichia coli. The consensus sequence of Tr1 binding motifs was A(C)/(T)TATA as determined with DNase I footprint assay. Tr1 showed a higher affinity towards the p28 promoter than the omp-1B promoter as determined with surface plasmon resonance. EcxR activated the tr1 expression in response to a temperature decrease. At 37°C low level of Tr1 activated the p28 expression. At 25°C high level of Tr1 activated the omp-1B expression, while repressing the p28 expression by binding to an additional site upstream of the p28 gene. Our data provide insights into a novel mechanism mediated by Tr1 regulating E. chaffeensis differential gene expression, which may aid in the development of new therapeutics for HME.